Methamphetamine Inhibits Long-Term Memory Acquisition and Synaptic Plasticity by Evoking Endoplasmic Reticulum Stress - Chen, Guang; Wei, Xiaoning; Xu, Xiang; Yu, Gang; Yong, Zheng; Su, Ruibin; Tao, Luyang (Frontiers in Neuroscience, 2021)
Methamphetamine (MA), an illicit drug abused worldwide, causes cognitive impairment. However, the detailed mechanisms underlying MA-induced neurologic impairment are still unclear. The present study aimed to investigate the mechanisms of MA-induced inhibition of memory acquisition from the perspective of endoplasmic reticulum (ER) stress. ER stress, caused by the accumulation of wrongly folded proteins in the ER, is important for new protein synthesis, which further influences the formation of long-term memory. A subacute methamphetamine poisoning model of mice was established and different behavioural experiments were performed, including the elevated plus maze, Morris water maze, electro-stimulus Y-maze, and novel object recognition tasks. The present results suggested that four-day exposure to MA inhibited long-term memory acquisition. Whereas, this damage to memory formation could be protected when mice were pretreated with ER stress inhibitor, tauroursodeoxycholic acid (TUDCA). The results of western blotting showed that subacute exposure to MA increased the protein levels of ER stress markers, such as binding immunoglobulin protein, phosphorylated eukaryotic translation initiation factor 2 α, cyclic AMP-dependent transcription factor (ATF)-6, ATF-4 and CCAAT-enhancer binding protein homologous protein. Meanwhile, the enhanced expression levels of these proteins were reversed by TUDCA, indicating that MA administration induced memory loss by evoking ER stress in the hippocampus. We also found that MA inhibited the induction of long-term potentiation in the hippocampus. Nevertheless, LTP could be induced when mice were pre-treated with TUDCA. In conclusion, MA inhibited long-term memory acquisition and synaptic plasticity via ER stress.